2018
DOI: 10.1177/2153368718802352
|View full text |Cite
|
Sign up to set email alerts
|

Race and the Likelihood of Intimate Partner Violence Arrest and Dual Arrest

Abstract: Research on the impact of race on the likelihood an incident of intimate partner violence will result in arrest is mixed. Some scholars find racial minorities to be at lower risk of arrest, some find racial minorities to be at higher risk of arrest, and some find no difference in arrest likelihood based on race of the involved parties. Using a data set comprising 10 years of National Incident-Based Reporting System data (2000–2009) from 5,481 jurisdictions in 36 states and the District of Columbia, the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 48 publications
4
12
0
Order By: Relevance
“…Due to the confounding nature of characteristics found in cases in which there are multiple victims and offenders, cases with more than two victims and more than two offenders were omitted. This approach is consistent with NIBRS research examining the likelihood of crime clearance (see, for example, Hirschel et al, 2021; McCormack & Hirschel, 2018; Roberts & Lyons, 2011; Walfield, 2016). As a result, the sample was reduced in size by 49,445 (1.8%) cases and 13 (0.2%) jurisdictions.…”
Section: Methodssupporting
confidence: 77%
“…Due to the confounding nature of characteristics found in cases in which there are multiple victims and offenders, cases with more than two victims and more than two offenders were omitted. This approach is consistent with NIBRS research examining the likelihood of crime clearance (see, for example, Hirschel et al, 2021; McCormack & Hirschel, 2018; Roberts & Lyons, 2011; Walfield, 2016). As a result, the sample was reduced in size by 49,445 (1.8%) cases and 13 (0.2%) jurisdictions.…”
Section: Methodssupporting
confidence: 77%
“…Moreover, coupled with fears of underenforcement in the police response to their victimization (McCormack & Hirschel, 2018; O’Neal, 2019), research finds that Black women may also face dual arrest (i.e., arrest of victim and offender) and police violence (Fedina et al, 2018; McCormack & Hirschel, 2018) when they report. Indeed, Black women are discredited and criminalized when they report their victimizations (Decker et al, 2019; Jacobs, 2017; McCormick & Hirschel, 2018). Historically, police were trained to associate Blackness with criminality—or “symbolic assailants”—as they conducted racialized police practices targeting Black people via slave patrols (Jones-Brown, 2007; Williams & Murphy, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Extralegal factors, such as alcohol involvement, have also predicted arrest (Dichter et al, 2011; Durfee & Fetzer, 2016; Hamilton & Worthen, 2011; Roark, 2016). In terms of race/ethnicity, some studies have demonstrated that arrest has increased in IPV incidents involving White victims when compared with other racial/ethnic groups (Dichter et al, 2011; Eitle, 2005; Hamilton & Worthen, 2011; McCormack & Hirschel, 2018).…”
Section: Police Response To Ipv and Stalkingmentioning
confidence: 99%